Catalogue of the Family Panorpidae (Mecoptera) in Canada, México and the United States - Dickson, Kathryn (Zootaxa, 2024)
Panorpa is the sole genus of the family Panorpidae (Mecoptera) occurring in North America. Here is presented a new catalogue that updates the list of Panorpa species present in Canada, México and the United States, last summarized by Penny and Byers (1979) and Penny (1997) and, for México, by Byers (2011) and Contreras-Ramos et al. (2014). In 1979 there were 46 species listed, but since then identifications of new species and new synonymies have brought the total count to 91 species. This catalogue provides for each species its valid name, complete bibliography, type specimen depository, type locality, distribution by province/state, and a synonymy of names applied.